THE INFLUENCE OF FAIRNESS AND SELF-ASSESSMENT SYSTEM ON TAX EVASION ON KPP PRATAMA WEST MAKASSAR - Jamali, Hisnol (Malaqbi Publisher, 2023)
This study aims to analyze the effect of justice and self assessment system on the action of tax evasion. Respondents in this study were individual taxpayers registered at the Primary Makassar Tax Service Office. The number of individual taxpayers who are the sample of this study is 100 taxpayers. The sample determination method used in the study is incidental sampling method. Data collection method through questionnaire, while data processing method used is multiple regression analysis. The results showed that the simultaneous justice and self assessment system had a positive and significant effect on the tax evasion action, justice partially had a negative and significant effect on the tax evasion action, the partial self-assessment system had a negative and significant effect on the tax evasion action.